TLR7 and IL-6 differentially regulate the effects of rotarod exercise on the transcriptomic profile and neurogenesis to influence anxiety and memory - Yun-Fen Hung; Yi-Ping Hsueh (iScience, 2021)
Summary: Voluntary exercise is well known to benefit brain performance. In contrast, forced exercise induces inflammation-related stress responses and may cause psychiatric disorders. Here, we unexpectedly found that rotarod testing, a frequently applied assay for evaluating rodent motor coordination, induces anxiety and alters spatial learning/memory performance of mice. Rotarod testing upregulated genes involved in the unfolded protein response and stress responses and downregulated genes associated with neurogenesis and neuronal differentiation. It impacts two downstream pathways. The first is the IL-6-dependent pathway, which mediates rotarod-induced anxiety. The second is the Toll-like receptor 7 (TLR7)-dependent pathway, which is involved in the effect of rotarod exercise on gene expression and its impact on contextual learning and memory of mice. Thus, although rotarod exercise does not induce systemic inflammation, it influences innate immunity-related responses in the brain, controls gene expression and, consequently, regulates anxiety and contextual learning and memory.